Indicators of non-performing loan: does efficiency matter? - Jiang, Tao; Zheng, Yanqiu (Technological and Economic Development of Economy, 2024)
The purpose of this study is to examine the impact of various factors on the level of non-performing loans (NPL) and, to determine the moderating role of efficiency on the relationship between different factors and NPL in China. The current study addressed four important factors to examine the role in relation to the NPL. These factors include; return on assets (ROA), return on equity (ROE), economic sustainability and political instability index. Furthermore, the moderating role of efficiency is addressed between these factors and NPL. Secondary data is used in this study to consider the empirical results. Secondary data related to ROA, ROE, economic sustainability and political instability index is collected from different sources. Consistent with the literature, we found significant effect of ROA, ROE, economic sustainability and political instability index on NPL. Banking sector of China is majorly influenced by these factors due to the effect on NPLs. Furthermore, the efficiency has contribution to the NPLs as moderating variable. Results of this study are helpful for the management of banking industry to resolve various issues related to NPLs.